Examining the teaching beliefs and practices of experienced ESL teachers: a sociocognitive-transformative perspective - Barrot, Jessie Saraza (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2016)
Examining language teacher beliefs and practices has been the subject of inquiry for the past 20 years. While some studies confirmed the consistency between teachers’ beliefs and practices, others also confirmed that beliefs are not always reflected in their classroom practices. It has also been found that teachers’ beliefs and practices do not always integrate the recent and established principles in second language teaching. To this end, this study sought to explore the teaching beliefs and practices of experienced ESL teachers and to determine whether these beliefs and practices run consistent with the current principles in ESL pedagogy from a sociocognitive-transformative perspective. For the stated purpose, five experienced ESL teachers were interviewed. The findings revealed that while there are consistencies between their beliefs and practices, some divergence were also observed. These results were attributed to several factors such as the abstractness of principles and attitude toward students. Implications for teacher education and future studies are discussed.